The role of lipocalin 2 in brain injury and recovery after ischemic and hemorrhagic stroke - Zhang, Jingwei; Wang, Zeyu; Zhang, Hao; Li, Shuwang; Li, Jing; Liu, Hongwei; Cheng, Quan (Frontiers in Molecular Neuroscience, 2022)
Ischemic and hemorrhagic stroke (including intracerebral hemorrhage, intraventricular hemorrhage, subarachnoid hemorrhage) is the dominating cause of disability and death worldwide. Neuroinflammation, blood-brain barrier (BBB) disruption, neuronal death are the main pathological progress, which eventually causes brain injury. Increasing evidence indicated that lipocalin2 (LCN2), a 25k-Da acute phase protein from the lipocalin superfamily, significantly increased immediately after the stroke and played a vital role in these events. Meanwhile, there exists a close relationship between LCN2 levels and the worse clinical outcome of patients with stroke. Further research revealed that LCN2 elimination is associated with reduced immune infiltrates, infarct volume, brain edema, BBB leakage, neuronal death, and neurological deficits. However, some studies revealed that LCN2 might also act as a beneficial factor in ischemic stroke. Nevertheless, the specific mechanism of LCN2 and its primary receptors (24p3R and megalin) involving in brain injury remains unclear. Therefore, it is necessary to investigate the mechanism of LCN2 induced brain damage after stroke. This review focuses on the role of LCN2 and its receptors in brain injury and aiming to find out possible therapeutic targets to reduce brain damage following stroke.